Strategi Membangun Komunikasi Yang Efektif Untuk Meningkatkan Kinerja Guru Di Sekolah - Meta Afra Niska; Nadila Desmiati; Ermita; Fifin Wildanah (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Effective communication plays an important role in improving teacher performance in schools. The purpose of this study is to understand strategies in improving effective communication in order to improve teacher performance. The research method used is a literature study by collecting, reviewing, and describing various scientific sources such as academic journals, books, and articles that discuss communication in the world of education and its influence on the performance of educators. The results of this study show that communication strategies such as open communication, two-way communication, utilization of technology, and interpersonal communication training contribute vitally to increasing teacher motivation and professionalism. The principal has a major role in building a pleasant school environment, listening to teacher aspirations, and providing constructive feedback. This study concludes that good communication strategies have a positive impact on teacher performance, increase collaboration between educators, and create a more effective learning environment.